Menegaskan Kembali Pembaruan Pemikiran Islam - Abdul Moqsith Ghazali (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
Problems faced by Muslim are increasingly complex. Challenges of modern life cannot be simply overcome by quoting the old religious interpretations, which are no longer irrelevant, but also have often created new problems. How many acts of terrorism, violence, discrimination, and de-humanization have been performed by referring to the religious texts? In fact, religious interpretation that destroys human values should be abandoned, and be replaced by interpretations which glorify and humanize human beings. One of main devices must be empowered for interpretation is reason (mind, ‘aql.) Through reason, a person not only can formulate relevant Islamic interpretation suitable to the era’s needs, but also can find the truth. Only by utilizing reason, amid strong tendency of scripturalism, Muslim people will succeed to create high civilization. Proven from human’s history, nations which have marginalized the role of reason would be in the darkness stage. Therefore, Islam continues to challenge mankind to use the reason. The prophet was sent to erect reason, and he says, “Al-dīn ‘aql lā dīna li-man lā ‘aqla lahu” (religion is reason, and no religion for who does not use the reason.)